A grammar of Moloko - Friesen, Dianne (Open textbook library., 2017)
This grammar provides the first comprehensive grammatical description of Moloko, a Chadic language spoken by about 10,000 speakers in northern Cameroon. The grammar was developed from hours and years that the authors spent at friends’ houses hearing and recording stories, hours spent listening to the tapes and transcribing the stories, then translating them and studying the language through them. Time was spent together and with others speaking the language and talking about it, translating resources and talking to Moloko people about them. Grammar and phonology discoveries were made in the office, in the fields while working, and at gatherings. In the process, the four authors have become more and more passionate about the Moloko language and are eager to share their knowledge about it with others.